Algunos aspectos fonéticos y morfológicos de las versiones latinas del libro de Rut - Jiménez Zamudio, Rafael (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
The author of this paper tries to display the several expedients which the translators of the Latin versions of the Bible used to adapt certain hebrew phonemes non-existent in Latin. It is also studied the morphological reorganization in the proper names because Hebrew has lost the case endings. To show these items we have chosen the Latin versions of the Book of Ruth.